Towards a New Consideration of the Integration of Translation in ESP Classes - Merine Asma; Salhi Ahmed (University of Eloued, 2022)
Translation, a basic means of communication, has been disfavored and even suffered the reputation of being an ill suited aid in teaching and learning English. In fact, there was a lot of research about the function of translation in language teaching and learning, some of which highlight its useless effect; however, other research present translation as the fifth language skill alongside the other four basic skills. With the birth of English for Specific Purposes (ESP) as a new trend in applied linguistics, an important question arises, is translation a necessary component in an ESP course? If yes, how does a teacher teach and include translation aspects in ESP classes? In fact, translation and its use in ESP classes have been subjected to numerous debates. The core issue in these considerations is whether or not translation needs to be included in ESP courses. Thus, the current theoretical study focuses on identifying the various reasons for the rejection of translation in EFL and ESP in the past. Moreover, the research seeks to reassess the role of translation in ESP classes and propose an approach or activities related to translation. All in all, the study will highlight a theoretical framework of some issues with implications for the integration of translation in ESP classes.
Intervention
Keywords: Communication; EFL; English for Specific Purposes; ESP; Language teaching and learning; Translation